Binder-free textile PAN-based electrodes for aqueous and glycerol-based electrochemical supercapacitors - Barbosa, Ingrid Ariani Belineli (2023)
Amidst different types of energy storage devices, electrochemical supercapacitors have received considerable attention as they close the gap between electrolytic capacitors and batteries. This work addresses electric double-layer capacitors (EDLCs), a type of electrochemical supercapacitor, and has been divided into two parts. In the former, the production and characterization of activated carbon fiber-felt (ACFF) electrodes derived from textile PAN-based fiber have been provided. In the latter, the electrochemical characterization of EDLCs in aqueous electrolytes (acidic and alkaline) and in three types of glycerol-based electrolytes have been investigated. Binder-free ACFF electrodes have a high specific surface area of 1875 m2 g-1, containing 87% of the total volume of pores as micropores (maximum pore width of 3 nm), and a modal distribution of 1.2 nm. Electrochemical impedance spectroscopy, cyclic voltammetry, and galvanostatic charge-discharge techniques were carried out in a symmetric two-electrode setup at room temperature. The results showed that ACFF electrodes are suitable for acidic and alkaline aqueous electrolytes as well as the choline chloride-glycerol hybrid electrolyte (ChCl:GLY) at a molar ratio of 3:1. Among aqueous electrolytes, H2SO4 2 mol L-1 had the most satisfactory electrochemical performance in terms of power and energy, followed by KOH 2 mol L-1 and H2SO4 1 mol L-1. Among the glycerol-based electrolytes investigated in this work, ChCl:GLY (3:1) has the most comparable performance to aqueous electrolytes. Although power density is still limited due to high internal resistance, ChCl:GLY (3:1) is heat-resistant and a promising alternative electrolyte for supercapacitors applications, especially given that glycerol is a by-product of FAME (fatty acid methyl ester) biodiesel.